2D-layered Mg(OH)2 material adsorbing cellobiose via interfacial chemical coupling and its applications in handling toxic Cd2+ and UO22+ ions. (September 2021) - Wang, Xin-Yu; Hao, Yang; Zhao, Hong-Bo; Guo, Yuan-Ru; Pan, Qing-Jiang
Abstract: The interfacial chemistry of nanocomposite materials is of overarching importance in the separation and purification science; moreover, its understanding helps to guide synthesis, clarify structure-property relationship and unearth novel applications. However, the composites feature rather complicated local structures and hydrogen bonds are often involved in the interface and the vicinity of active sites. In this regard, density functional theory first-principle calculations associated with experimental study have synergistically examined two-dimensional (2D) magnesium hydroxide material with different layers and their adsorption toward cellobiose. Hydrogen bonds are found responsible for the interfacial coupling, which make it vital to cover the dispersion correction in the calculation. The average adsorption energy ranges from −0.29 to −0.35 eV, falling well within the range of reported hydrogen-bonding strength. On the basis of calculated structural/interfacial properties and experimental findings, the 2D Mg(OH)2 in terms of three-layer model was unraveled to substitute toxic Cd 2+ ion and sorb radioactive UO2 2+ that is coordinated by water and hydroxyl groups. These reactions are thermodynamically feasible. The ion-exchanging mechanism was proposed for cadmium removal and the outer-sphere adsorption one for uranium extraction. Graphical abstract: The first-principle computation and experiment synergistically recognized local structures of 2D Mg(OH)2 -cellobiose composite and the hydrogen-bond-dominated interfacial coupling. Mechanisms of ion exchange and inner-sphere adsorption were revealed while applying Mg(OH)2 to handle toxic Cd 2+ and radiotoxic UO2 2+, respectively. Image 1 Highlights: Mg(OH)2 -cellobiose composite was synthesized and calculated by DFT. Local structures controlled by chemical interfacial coupling were recognized. The interfacial coupling was proved as hydrogen bond nature. Reactions of Mg(OH)2 with toxic Cd 2+ and UO2 2+ ions are thermodynamically favored. Ion-exchange and inner-sphere adsorption mechanisms were revealed.